2014
DOI: 10.1093/nar/gku503
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of L1 expression and retrotransposition by melatonin and its receptor: implications for cancer risk associated with light exposure at night

Abstract: Expression of long interspersed element-1 (L1) is upregulated in many human malignancies. L1 can introduce genomic instability via insertional mutagenesis and DNA double-strand breaks, both of which may promote cancer. Light exposure at night, a recently recognized carcinogen, is associated with an increased risk of cancer in shift workers. We report that melatonin receptor 1 inhibits mobilization of L1 in cultured cells through downregulation of L1 mRNA and ORF1 protein. The addition of melatonin receptor ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 87 publications
(143 reference statements)
3
50
0
Order By: Relevance
“…1 Our recent findings illustrate several novel features of L1 biology directly relevant to human health. Specifically, we highlight a new dimension to the complex regulation of both L1 expression and damage through the unforeseen connection between L1, the host's circadian system, and environmental light exposure at night in vivo.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…1 Our recent findings illustrate several novel features of L1 biology directly relevant to human health. Specifically, we highlight a new dimension to the complex regulation of both L1 expression and damage through the unforeseen connection between L1, the host's circadian system, and environmental light exposure at night in vivo.…”
mentioning
confidence: 62%
“…1 Analysis of endogenous human L1 expression in PC3-derived xenografts perfused with human blood collected at noon or midnight as well as at night after exposure to bright light demonstrated that night-time blood suppresses L1 expression. The addition of exogenous melatonin to melatonin-poor blood during perfusion suppressed L1 expression; while the addition of non-selective antagonist of melatonin receptors during perfusion with melatonin-rich blood restored detection of L1 mRNA in tumor samples.…”
mentioning
confidence: 99%
“…L1 expression and retrotransposition are suppressed by many diverse cellular pathways in order to minimize the genomic damage inflicted by L1 activity [20,[43][44][45][46][47][48][49][50]. L1 encodes an ORF2 protein with several identified functions essential for the retrotransposition process.…”
Section: Discussionmentioning
confidence: 99%
“…The Belancio laboratory has recently reported that melatonin, via the MT 1 receptor mediated action, suppresses expression of the endogenous retrotransposon L1 in a tissue-isolated model of human cancer (Deharo et al 2014). This finding supports that LEN-induced suppression of nocturnal melatonin synthesis activates L1 expression.…”
Section: Melatonin Regulation Of Genomic Instabilitymentioning
confidence: 99%